EFFECT OF HEAT TREATMENT ON PHYSICAL AND MECHANICAL PROPERTIES OF SOME WOOD SPECIES (Innovation in Woodworking Industry and Engineering design, 2026)
In this article described research of physical and mechanical properties of some wood species, that were heat treated through Russian thermoconvective timber dryer (temperature up to 185 ºС) in comparison with untreated wood. Afterwards, moisture content, density, shrinkage, swelling, ultimate strength in compression parallel the grain, static bending strength, impact bending strength, static hardness, moisture absorption, water absorption of the specimens were measured and compared to the properties of untreated wood.